2019
DOI: 10.1007/s13300-019-0569-7
|View full text |Cite
|
Sign up to set email alerts
|

Treating Patients with Type 2 Diabetes Mellitus Uncontrolled on Basal Insulin in the Czech Republic: Cost-Effectiveness of IDegLira Versus iGlarLixi

Abstract: Introduction Few patients with type 2 diabetes mellitus (T2DM) achieve recommended glycemic control targets in the Czech Republic. Novel therapies, such as fixed-ratio combinations of basal insulin plus glucagon-like peptide-1 receptor agonists, may contribute to better glycemic control. In the analysis presented here, the present analysis assessed the long-term cost-effectiveness of two fixed-ratio combinations, IDegLira (insulin degludec/liraglutide) and iGlarLixi (insulin glargine/lixisenatide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…To date, one other cost-effectiveness analysis comparing IDegLira with iGlarLixi has been published. This analysis in the Czech Republic produced similar outcomes to the present analysis in Italy 41. IDegLira was associated with improved clinical outcomes and increased costs compared with iGlarLixi, but was likely to be considered cost-effective in the Czech Republic.…”
Section: Discussionsupporting
confidence: 75%
“…To date, one other cost-effectiveness analysis comparing IDegLira with iGlarLixi has been published. This analysis in the Czech Republic produced similar outcomes to the present analysis in Italy 41. IDegLira was associated with improved clinical outcomes and increased costs compared with iGlarLixi, but was likely to be considered cost-effective in the Czech Republic.…”
Section: Discussionsupporting
confidence: 75%
“…Previous publications have reported on cost-effectiveness estimates for iDegLira versus iGlarLixi from Italian and Czech Republic perspectives. In the Italian estimate, iDegLira was associated with an incremental cost of €930 and a gain of 0.13 QALYs [ 31 ], while in the Czech Republic the incremental cost was estimated to be CZK 94,029 (£3164) for the iGlarLixi 100/33 (30–60) pen and CZK 47,058 (£1583) for the iGlarLixi 100/50 (10–40) pen, with a gain of 0.14 QALYs [ 32 ]. These cost estimates are qualitatively different from those presented in this UK analysis, which consistently demonstrated iGlarLixi to be less expensive than comparators, but in both analyses, the ICER estimates for iDegLira were well below local WTP thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, iDegLira was associated with a greater reduction in HbA1c and body weight and a lower risk of severe hypoglycemia; however, using the ADA definition of symptomatic hypoglycemia for both studies, no significant difference was observed between treatments [51]. Moreover, other analyses have recently found iDegLira to be costeffective compared to iGlarLixi in patients with uncontrolled T2DM on BI due to reduced incidence and delayed onset of complications [52,53].…”
Section: 6mentioning
confidence: 73%